Medicine on the periphery : public health in Yucatán, Mexico, 1870-1960 - Sowell, David, 1952- (Lexington Books, 2015)
Medicine on the Periphery traces the development of Yucatán's medical institutions, public health programs, healers, and changing disease environment from the 1870s through 1960. The biomedicalization of Yucatán's public health system is analyzed within the Atlantic medical community and the emerging revolutionary state of central Mexico.